Stress corrosion cracking behaviors of FV520B stainless steel used in a failed compressor impeller. (October 2020) - Nie, Defu; Chen, Xuedong; Wu, Qiaoguo; Liu, Yan
Highlights: FV520B steel is slightly susceptible to aqueous brine solution, which increases with temperature. Tempered martensite and δ ferrite show significant SCC susceptibility in NACE solution A at 25–75 °C. K IC of the steel is 150MPam 1/2 in air, but K ISCC dramatically reduces to 48MPam 1/2 in NACE solution A. A modified Boltzman equation is proposed to describe SCC propagation rate ( da/dt versus K ) curves. Fractures of the SSRT specimen and the impeller are simulated based on ABAQUS and ZENCRACK software. Abstract: Stress corrosion cracking (SCC) in compressor impellers made of FV520B stainless steel frequently occurred, and hence was investigated by slow strain rate tests (SSRTs) and fracture toughness tests, combined with finite element analysis (FEA) based on ABAQUS and ZENCRACK software. SSRTs revealed that the FV520B stainless steel had slight susceptibility to aqueous brine solution, which increased with increasing temperature, and fracture surface exhibited ductile feature with dimples similar to that in nitrogen; however, this material showed significant susceptibility to NACE solution A at various temperatures, and fracture surface consisted of initial quasi-cleavage region and subsequent dimple region; both tempered martensite matrix and localized δ ferrites were susceptible to SCC. Fracture toughness K IC ( J IC ) of this steel was 150MPam 1/2 (102KJ/m 2 ) in air, but threshold stress intensity factor ( KISCC ) dramatically reduced to 48MPam 1/2 in NACE solution A, and Boltzman equation was modified to describe SCC propagation rate ( da/dt-K ) curves. Comparison with FEA results indicated that the fracture of SSRT specimen was initially affected by environmental factor and then mainly attributed to mechanical factor, whereas the whole fracture process of impeller was closely related to corrosive environment. This study was useful for SCC evaluation of materials and failure analysis of compressor impellers.